Edukasi Dampak Positif Bahan Organik bagi Keseimbangan Ekologi dalam Membangun Ekosistem Berkelanjutan - Agus Yadi Ismail; Sri Ayu Andayani; Suwari Akhmaddhian; Sukron Aminudin (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
This Community Service Activity aims to increase participants' understanding of the positive impact of organic matter on ecological balance and its application in sustainable agriculture. The workshop was carried out with a participatory education method involving 36 participants from six districts in West Java, through material presentations, interactive discussions, and simple demonstrations. Evaluation is carried out without a pretest and posttest, but through observation, interaction, and evaluation sheets with the categories of understanding level